A comparative approach shows differences in patterns of numt insertion during hominoid evolution (2009)
ABSTRACT: Nuclear integrations of mitochondrial DNA (numts) are widespread among eukaryotes although their prevalence differs greatly among taxa. Most knowledge of numt evolution comes from analyses of whole genome sequences of single species, or more recently from genomic comparisons across vast phylogenetic distances. Here, we employ a comparative approach using human and chimpanzee genome sequence data to infer differences in the patterns and processes underlying numt integrations. We identified 66 numts that have integrated into the chimpanzee nuclear genome since the human-chimp divergence, which is significantly greater than the 37 observed in humans. By comparing these closely related species, we accurately reconstructed the pre-integration target site sequence, and deduced nucleotide changes associated with numt integration. From over 100 species-specific numts, we quantified the frequency of small insertions, deletions, duplications, and instances of microhomology. Most human and chimpanzee numt integrations were accompanied by microhomology and short indels of the kind typically observed in the nonhomologous end-joining pathway of DNA double-strand break repair. Human specific numts have integrated into regions with a significant deficit of transposable elements, while the same was not seen in chimpanzees. From a separate dataset, we also found evidence for an apparent increase in the rate of numt insertions in the last common ancestor of humans and the great apes using a PCR-based screen. Lastly, phylogenetic analyses indicate that mitochondrial numt alignments must be at least 500bp, and preferably greater than 1kb in length, in order to accurately reconstruct hominoid phylogeny and recover the correct point of numt insertion.